KEPENTINGAN INDONESIA DALAM MERATIFIKASI ASEAN AGREEMENT ON TRANSBOUNDARY HAZE POLLUTION PADA TAHUN 2014 INDONESIA’s INTEREST IN RATIFYING ASEAN AGREEMENT ON TRANSBOUNDARY HAZE POLLUTION(AAT - Ovi Dwi Rahmawati (HI 16 UMY 142, 2016)
*142 This journal aims to explain the factors that affect Indonesia decision to ratify the Asean Agreement of Transboundary Haze Polution. Asean Agreement of Transboundary Haze Polution is a soft law that control the haze pollution in South East Asia region. 10 countries of ASEAN member has already ratify this agreement until 2014. Indonesia decided to ratify the Asean Agreement of Transboundary Haze Polution on 2014. There are 3 factors that affect Indonesia to ratify the agreement. The 3 factors are domestic politics, economy, and international context.